Магнітні властивості наномагнетиту, синтезованого в температурному діапазоні 40-90 ºC - Дудченко, Н.О. (Мінералогічний журнал, 2011)
Зразки синтетичних аналогів біогенного магнетиту отримано за двома технологіями співосадження солей дво- та тривалентного заліза гідроксидом калію в діапазоні значень температури (40—90 °C). Перша технологія полягала у співосадженні суміші сульфату заліза (II) та хлориду заліза (III), друга — хлориду заліза (II) та хлориду заліза (III). Визначено намагніченість насичення усіх синтезованих зразків. Показано, що намагніченість насичення наномагнетиту прямо залежить від температури синтезу. Отримані результати можуть бути використані для подальшого розвитку технологій створення синтетичних аналогів біогенного магнетиту. Образцы синтетических аналогов биогенного магнетита были синтезированы согласно двум технологиям соосаждения солей двух- и трехвалентного железа гидроксидом калия в температурном диапазоне 40—90 °C. Первая технология состояла в соосаждении смеси сульфата железа (II) и хлорида железа (III), вторая — хлорида железа (II) и хлорида железа (III). Показано, что намагниченность насыщения наномагнетита прямо зависит от температуры синтеза. Полученные результаты могут быть использованы для дальнейшего развития технологий создания синтетических аналогов биогенного магнетита. As is generally known, the organism of human beings and the organisms of other animals contain magnetite (Fe₃O₄). Biogenic magnetite — is the object of nano mine ralogy that has unique magnetic properties. It is known, that biogenic magnetite is the biomineral that ensures the navigation properties of animals (birds, fish, insects, etc.) and takes part in processing and saving of information in the brain tissues. But it is yet not known about the rea lization of magnetoreception in the organisms. The inves tigation of magnetic biominerals opens wide perspec tives for creation of synthetic analogues of the physiological particles as hybrid of mineral and organic matter. There are many technologies used for the magnetite nanoparticles creation. We have synthesized magnetite nanoparticles by two technologies of iron salts co-pre cipitation by potassium hydroxide at different temperatures (40—90 °C). First technology includes precipitation of iron (II) sulfate and iron (III) chloride mixture. Second technology includes precipitation of iron (II) chloride and iron (III) chloride mixture. It was shown, that the higher temperature of the reaction, the higher the magnetization of obtained nanomagnetite. The obtained results could be used when developing the technologies of biomimethic synthesis of biogenic magnetite analogues.